Isolated noncompaction of the ventricular myocardium - Narin, Nazmi; Çeliker, Alpay; Üzüm, Kazım; Poyrazoğlu, M. Hakan; Karakükçü, Musa (The Turkish Journal of Pediatrics, 2002)
Noncompaction of the ventricular myocardium is a rare congenital disorder characterized by the presence of numerous prominent trabeculations and deep intertrabecular recesses which communicate with the left ventricular cavity. The disease uniformly affects the left ventricle, and sometimes also affects the right ventricle. Echocardiographic findings are important clues for the diagnosis. Clinical symptoms include signs of left ventricular systolic dysfunction even to the point of heart failure, ventricular arrhythmias, and embolic events. We describe an illustrative case of isolated noncompaction of the left ventricular myocardium in a two-year-old child with the typical clinical and echocardiographic features of the disease. The literature on the topic is reviewed.
Keywords: noncompaction; myocardium